Planning Mechanisms for Regional Electric Power Supply System Development - Malyshev, Evgeniy Anatolyevich; Kashurnikov, Anton Nikolayevich (Economy of Regions, 2015)
Key problems of the regional electric power supply systems are examined. These problems result from a lack of regulated interaction mechanisms for uniting the different entities’ resources aimed at the realization of investment activities. One of the main problems of the power supply industry is physical and moral aging of both generating and networking equipment. In the article, the necessity of management system formation to control the development of power sector has been proved. The deficiencies of the modern investment procedure in power companies are described. The absence of continuity between the regional and local strategic planning documents and investment planning of a power company has been found out. The possibility to develop a new mechanism for attracting investment has been proposed. The regulation of joint activities to implement the development program for the regional power supply industry has been proposed. The management system to develop the Russian power industry has been proposed. The comparative analysis of generating capacity development mechanisms has been carried out, such as capacity supply agreement (CSA), investment support mechanism (ISM), and long-term power market (LPM). The interaction procedure of the planning of the power supply infrastructure development has been described. The mechanism connecting the state sectoral and regional planning and corporate planning of power supply infrastructure development has been proposed. The regional aspects of industrial policy and its legislative support have been considered. To successfully implement the public-private-partnership (PPP) projects, it is necessary to create the effective PPP model within the federal and regional legislation framework; to develop the financial model providing the recoverability of investments; to provide a mutually beneficial cooperation between executive bodies and private investors. The possibility to apply the PPP mechanism for regional power supply infrastructure development have been validated. The PPP mechanism application can help to solve the problem of regional and interregional power supply infrastructure development, as it is of vital importance for the regions of Siberia and the Far East.